Tax policy of the emirate in the Shakhrisabz bekdom at the end of the 19th - beginning of the 20th centuries - Kamalova, Xabiba (The Lingua Spectrum, 2025)
This article provides information that in the late 19th and early 20th centuries, the population of the Shahrisabz bekdom was forced to pay about 40 taxes, and the Emir of Bukhara's desire to oppress the population of Shahrisabz in various ways and increase the amount of taxes caused an economic crisis in the country and caused discontent and uprisings among the people.